SOLUTIONS TO THE H-INFINITY GENERAL DISTANCE PROBLEM WHICH MINIMIZE AN ENTROPY INTEGRAL - Mustafa, D; Glover, K; Limebeer, D (1991)
We pose, and solve, the problem of minimizing the entropy of an H∞-norm bounded and stabilized closed-loop. Solution proceeds via the equivalent error system distance problem. The central member of the admissible class is shown to minimize the entropy at infinity, and in that case an explicit state-space formula is derived for the minimum value of the entropy. Links between entropy, H2-norms and H2-optimal control are given. © 1990.